Impact of Four Week Swimming Exercise with Alpha-Tocopherol Supplementation on Fertility Potential in Healthy Rats - Kalantari, Abolfazl; Saremi, Abbas; Shavandi, Nader; Foroutan Nia, Ali (Urology Journal, 2017)
Purpose: The aim of this study was to evaluate the effect of 4 week intensive swimming exercise and alpha-tocopherol supplementation on testicular oxidative stress and spermatogenesis in rats. Materials and Methods: 40 male rats were randomly assigned to Control (C), Sham (S), Exercise (E) and Exercise + supplement (ES) groups. Exercise training performed for 4 weeks (1session/day, 6days/week). Each session included 180 minutes of swimming. In ES group, alpha-ocopherol was injected at a dose of 50 mg/kg/day. 48 hours after last training session, all rats were killed and gonads of them were removed from their body for histological and biochemical assays. All statistical analysis was performed by SPSS 16. P values less than 0.05 were considered as statistically significant. Results: Total testicular antioxidant capacity increased significantly in E (P = .003) and ES groups (P = .001) whereas there was no significant difference between C and E group in testicle Malondialdehyde (a lipid peroxidation marker) level (P = .999) and spermatogenesis quality (P = .381). Testicle Malondialdehyde level decreased (P = .009) and spermatogenesis quality was improved significantly in ES group (P = .001). Conclusion: Alpha-tocopherol supplementation is effective in order to improve spermatogenesis process in athletes who exercise with high intensity.